No Significant Association between 25-OH Vitamin D Status and SARS-CoV-2 Antibody Response after COVID-19 Vaccination in Nursing Home Residents and Staff - Eline Meyers; Evelien De Smet; Hanne Vercruysse; Steven Callens; Elizaveta Padalko; Stefan Heytens; Linos Vandekerckhove; Piet Cools; Wojciech Witkowski (Vaccines, 2023)
Vitamin D is an essential nutrient for various physiological functions, including immunity. While it has been suggested that higher vitamin D levels/supplementation are associated with a better immune response to COVID-19 vaccination, conflicting data exist. Therefore, we aimed to investigate the association between vitamin D (25-hydroxyvitamin D) deficiency/supplementation, and SARS-CoV-2 antibody responses post-vaccination in nursing home residents (NHRs) and staff (NHS). Blood samples were collected from 115 NHRs and 254 NHS at baseline and 14 days after primary course BNT162b2 vaccination. Baseline samples were assessed for serum 25-hydroxyvitamin D levels, while follow-up samples were analyzed for spike protein S1 receptor-binding domain (S1RBD) IgG antibody concentrations and 50% pseudoneutralization titers. Vitamin D supplementation status was obtained from NHRs medical records. We compared immune responses between (severe) vitamin D-deficient and -sufficient NHRs/NHS and between supplemented and non-supplemented NHRs, stratified for history of SARS-CoV-2 infection and participant type. No significant differences in either binding or neutralizing COVID-19 vaccine antibody response were found between groups. The prevalence of vitamin D deficiency (<20 ng/mL) was 45% (95% CI: 36–54%) among NHRs and 60% (95% CI: 54–66%) among NHS. Although we showed that vitamin D status may not be related to a better COVID-19 vaccine antibody response, addressing the high prevalence of vitamin D deficiency in the nursing home population remains important.